2016
DOI: 10.1007/s10876-016-1133-5
|View full text |Cite
|
Sign up to set email alerts
|

From Cs2Mo6Cl14 to Cs2Mo6Cl14·H2O and Vice Versa: Crystal Chemistry Investigations

Abstract: International audienceWe report here the synthesis, the crystal structure and the luminescent properties of the new cluster compounds Cs2Mo6Cl14·H2O and Cs2Mo6Br14·H2O. Single-crystal X-ray diffraction performed on Cs2Mo6Cl14·H2O indicates that the compound crystallizes in the monoclinic space group C2/c with refined cell parameters a = 19.578 Å, b = 15.151 Å, c = 9.347 Å, and β = 115.64°. The structure can be described from discrete [Mo6Cl8iCl6a]2- anionic cluster units arranged in a “A–A’–A–A’” pseudo prisma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 54 publications
3
22
0
Order By: Relevance
“…The CMC cluster unit was prepared according to a procedure already reported that combined the use of solid-state and solution chemistries [41,42] [43]. Besides, the remarkable patterns of the ZnO phase formed on the brucite-like sheets were also verified with the peaks at the 2θ angles of 32 o , 34 o , and 36 o in this study [43].…”
Section: Synthesis Of Mo 6 @Ldh-1 and Mo 6 @Ldh-2 Nanocompositessupporting
confidence: 71%
See 1 more Smart Citation
“…The CMC cluster unit was prepared according to a procedure already reported that combined the use of solid-state and solution chemistries [41,42] [43]. Besides, the remarkable patterns of the ZnO phase formed on the brucite-like sheets were also verified with the peaks at the 2θ angles of 32 o , 34 o , and 36 o in this study [43].…”
Section: Synthesis Of Mo 6 @Ldh-1 and Mo 6 @Ldh-2 Nanocompositessupporting
confidence: 71%
“…However, the photoluminescent intensity of the Mo 6 cluster is not strong in the spectrum of Mo 6 @LDH-2, this is due to the significant change in the apical halogen ligand of the CMC cluster. As known, theA c c e p t e d m a n u s c r i p t photoluminescent property of the Mo 6 cluster is decreased when the apical halogen ligands are replaced by H O molecules or hydroxyl anion[32,41,45].…”
mentioning
confidence: 99%
“…The secondary phase was assigned to be Cs2[Mo6Cl14].H2O as reported in a separate report. 39 As the fraction of this secondary phase in the currently prepared sample should be negligibly small, we assume that the obtained results represent the characteristics of the trigonal Cs2[Mo6Cl14] phase. The refined lattice parameters of each sample, listed in Table 1, were almost identical to those reported in literature, 38−40 being only slightly smaller.…”
Section: Structural Analysesmentioning
confidence: 99%
“…38−40 After purification, all samples were heated at 150 °C for 1 h in a glove box filled with dry N2 gas (< 0.1 ppm H2O). In our previous study, 38,39 41 the observed spectra were fitted by mixed Gaussian-Lorentzian functions using the method of least squares to calculate the integrated peak intensities and relative shifts of peak positions.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The unique photochemistry of the molybdenum and tungsten halide clusters [M 6 X 8 Y 6 ] 2À (M = Mo, W; X, Y = Cl, Br, I) has been known for over 30 years (Maverick et al, 1983) and researchers continue to explore the tunabilty of the redox potentials, crystal structures and photochemical properties of cluster-containing compounds via variation of the bridging and terminal ligands and the counter-ion (Mikhailov et al, 2016;Saito et al, 2017;Akagi et al, 2018). Metal clusters, such as molybdenum halides, consist of an inner [Mo 6 X 8 ] 4+ core surrounded by six axial ligands which are more labile than the core ligands, making the preparation of mixed-ligand cluster complexes relatively straightforward.…”
Section: Chemical Contextmentioning
confidence: 99%